The evaluation of quality of library services: Gender perspective in public services - Ramadhan, Ndaru; Setiawati; Hasanah, Ayunia; Centia, Selvi (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Libraries, as public service providers, have an obligation to provide excellent service. Evaluation of the quality of public services from a gender perspective can help policymakers to develop gender-based services, retain current service users, and attract new service users. Purpose: To evaluate the quality of library services at the Balai Yanpus DPAD DIY from a gender perspective and to prepare recommendations for improvements for the Balai Yanpus DPAD DIY. Method: This research uses quantitative methods and data collection techniques through questionnaires with 270 respondents. Data was analyzed using gap analysis, conformity analysis, and visualization using the Importance Performance Analysis (IPA) method via SPSS Version 26 software. Findings: Based on the gap and conformity analysis results, it is known that female and male respondents have different service quality indicators that are considered to meet users expectations. There are 5 indicators for female users and 6 indicators for male users that have succeeded in meeting the expectations. These indicators also have a level of conformity value exceeding 100%. The results of the IPA Matrix analysis of male and female service users also show that there are 5 indicators in Quadrant 3 so that they require improvement even though they are not the main priority. Conclusion: This study concludes that the quality of library services at Balai Yanpus DPAD DIY still needs to be improved in order to achieve maximum public satisfaction and provide excellent services. This study contributes to the development of studies related to public services and library science by taking a gender perspective in its analysis.